An approach for evaluating and mitigating intra-application I/O performance variability over parallel file systems - Inacio, Eduardo Camilo (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2019.